Pengaruh Penambahan Kapur Dan Abu Batu Bata Terhadap Nilai Kuat Tekan Bebas Dan CBR Pada Tanah Lempung Kecamatan Tenayan Raya - Prayogo, Giri; Nugroho, Soewignjo Agus; Fatnanta, Ferry (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A Tenayan Raya subdistrict is an area where there is an adequate thick of clay layer. This condition is seen during rain that the soil become softer, while in dry conditions there are many cracks on that soil. In case, it can cause some damages to the building due to the tilt of the building's foundation as an effect of shrinkage soil. Tenayan Raya also known as a brick production area. The brick production process may generate ash as a waste of brick kilns which has not been utilized optimally. This study aims to utilize brick ash as an additive material to improve clay properties in term of reducing its shrinkage feature. A certain amount of brick ash were mixed to clay soil and lime also were two added as a companion of a stabilizing agent. Some variation properties of two additive materials were applied in the sample of UCS and CBR tests. The effect of curing and soaking time was also be checked in term of UCS and CBR value changed. Based on properties tests, the clay soil classified standard. The mixture of 80% clay + 10% lime + 10% brick ash, in OMC condition, has the maximum of UCS and CBR laboratory test value. Curing and soaking time also has a significant contribution in increasing UCS and CBR value. The maximum value of both tests was reached at day 7th of curing and soaking time.Keywords : Clay, Swelling, Stabilization, Lime, Brick ash, Soil bearing capacity